PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA BANK RAKYAT INDONESIA CABANG ADISUCIPTO YOGYAKARTA - Hakim Hakim; Selamat Muliadi (Jurnal Manajemen dan Profesional, 2020)
Service quality is a fundamental factor in a company engaged in the service sector, in this case BRI Branch Adisucipto Yogyakarta Cilacap. Customer satisfaction can be seen from each level of service provided massively. The results of this study indicate that the validity and reliability instrument testing for all service variables, Tangibles (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), and Emphaty (x5) has taken care of the provisions. Meanwhile, from the test results the value of 17.157 and F table of 2.47 with a significance of 0.000. Therefore (17.157> 2.47) with a significance value less than 0.05 (sig responsiveness (Responsiveness), guarantee (Assurance) and empathy (Emphaty) to customers at the Kawunagnten Cilacap Branch of BRI Bank. And for testing the / R square gets 0.477, which means that the Tangible, Reliability, Responsiveness, Assurance and Emphty variables in this study can serve customers by 47.7% while the remaining 53.3% are from other variables outside the independent variables. From this research, the conclusion is that the customers of BRI Adisucipto Yogyakarta Branch are quite satisfied with the services provided, but there are several things that are important and need to be considered such as the Tangibles variable because physical evidence is abstract and must be felt directly by the customer. Tangibles quality of service, including adequate physical appearance of the room (waiting room, seating, comfortable interior), parking for service counters and electronic and communication infrastructure must be available so that the customer does not become difficult if the customer wants to connect with the Bank through the telephone network.